Sprint-like cardiac dynamics support repeated acrobatic lunges in foraging rorqual whales - Ashley M. Blawas; James Fahlbusch; Jack Barkowski; David E. Cade; John Calambokidis; Ari S. Friedlaender; Brandon Southall; Paul J. Ponganis; Jeremy A. Goldbogen (Proceedings of the National Academy of Sciences, 2026)
The dive response decreases heart rate, regulates blood flow distribution, conserves oxygen, and extends dive duration. In diving animals, dive heart rate can be modulated to meet increased demands of exercise during foraging. However, lunge-feeding rorquals represent an extreme example of exercise under breath-hold conditions: Though most of their dive time is spent gliding and filtering, lunges require high-power, acrobatic sprints to engulf massive volumes of prey-laden water. Our biologging data show that heart rate repeatedly increases with lunging but only gradually declines during filtering, dissimilar from the heart rate-activity coupling observed in other divers. We suggest that the unique nature of rorqual exercise likely requires glycolytic metabolic substrates, rather than aerobic substrates, during short, powerful lunges. During slow filtering, high heart rates may help partially renew these energy sources via oxygen-dependent pathways. By temporarily buffering oxygen demand from supply, the flexible dive response appears to optimize oxygen use in lunging rorquals and support aerobically “cheap” foraging. The data also show that dive cycle heart rate scope increases with rorqual size. We propose that cardiovascular plasticity during high and low power phases of foraging dives underpins rorquals’ ability to achieve high foraging efficiencies and combine explosive predation with grazing-like efficiency in a single lineage.